Assessment on housing affordability on selected urban areas in Perak - Mohamed Osman, Mariana; Shuid, Syafiee; Bachok, Syahriah; Muhamad Yusop, Siti Wahidah (American Scientific Publishers, 2017)
This study concerns on strategies and focuses on affordable housing for urban areas in Perak. The affordable housing development has become an absolute necessity of residents in Perak. The affordable housing assessment is to assist policy formulation, decision-making and resources allocation of the local authorities and state government. It was found based on national household income survey for the year 2012 to 2014 that household income levels differed from one district to another, with Kinta and Manjung population having higher income levels compared to the rest of the state population. Analysis of the study appears to show that some 40% of the population earned less than RM 4,000 monthly, thus, can be classified as the B40 group and there existed disparities among districts which resulted in differing levels of affordability, particularly in the context of purchasing of a house. Furthermore, the study also found that there has been a drastic change in housing pricing between the year of 2012 and 2014 that affected the affordability levels. In other words, the affordability index for the whole of Perak for the year 2014 and 2015 can be categorised as severely unaffordable.